Accelerometric analysis of head impacts in amateur wrestling: An exploratory analysis - Hecimovich, M.; King, D.; Garrett, T. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
PURPOSE: The aim of this exploratory study was to investigate the frequency, magnitude and distribution of head impacts greater than 10 g with the use of wireless head impact sensors over a single tournament in a small sample of adult collegiate wrestlers. METHODS: Three participants wore an impact-sensing skin patch on their mastoid process during each match. The patch contained a low-power, high-g triaxial accelerometer with 200 g maximum per axis and a triaxial angular rate gyroscope to capture linear and rotational time history accelerations of the heads center of gravity for all impacts that occurred during the matches. Head impact exposure including frequency, magnitude and location of impacts were quantified using previously established methods. Two measures of impact frequency were computed for each participant: impacts per match, the total and average number of impacts per match for all matches; participant group impacts, the total and average number of recorded head impacts for the three participants` groups for all matches. Head impacts were assessed for injury tolerance level for a concussion occurring using previously published injury tolerance levels for linear (>95 g) and rotational acceleration (>5,500 rad/s2). Head impacts were assessed for impact severity using previously published levels for linear acceleration (mild <66 g, moderate 66-106 g, severe >106 g) and rotational acceleration (mild <4,600 rad/s2, moderate 4,600-7,900 rad/s2, severe >7,900 rad/s2). RESULTS: Participants averaged 41 ± 4 impacts with a resultant median peak linear and rotation acceleration of 15 g and 1,880 rad/s2 resulting in a median HITSP and the RWECP of 15 and 0.0004, respectively. The location of impacts varied considerably with more head impacts to the front of the head than the back and top. CONCLUSIONS: Due to the exploratory nature of this study, small sample size and the absence of a diagnosed concussion, the results are to be viewed with caution, as it is unclear of the generalizability of the data. Results indicate lower levels in all measurements compared to football and rugby. Interestingly the back of the head recorded higher median peak linear accelerations then the side that may be the result of takedown maneuvers. This may have also contributed to the higher median RWECP of the top right side of the head than of the front right side. The key to this study was obtaining and thus gaining initial measurements on the frequency, magnitude, distribution and risk weighted exposure of head impacts in collegiate wrestling in order to assist in the identification of at-risk wrestlers and better inform medical personnel of the need to evaluate an athlete for concussion.